2012
DOI: 10.1021/nn302633q
|View full text |Cite
|
Sign up to set email alerts
|

Design Aspects of Bright Red Emissive Silver Nanoclusters/DNA Probes for MicroRNA Detection

Abstract: The influence of the nucleic acid secondary structure on the fast (1 h) formation of bright red emissive silver nanoclusters (AgNCs) in a DNA sequence (DNA-12nt-RED-160), designed for the detection of a microRNA sequence (RNA-miR160), was investigated. The findings show that especially the propensity for mismatch self-dimer formation of the DNA probes can be a good indicator for the creation and stabilization of red emissive AgNCs. Also, the role of the thermal stability of the secondary DNA structures (mismat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
172
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 177 publications
(182 citation statements)
references
References 42 publications
7
172
0
Order By: Relevance
“…If bases contained within the 5′-end of the target binding domain participate in cluster formation, this insertion would destabilize the conformation of the bases and inhibit or alter cluster formation. 30 Doing so completely inhibited AgNC formation in the presence of target for all six target sequences tested (see ESI †), further supporting the notion that the 12-base AgNCstabilizing sequence requires additional bases to stabilize a fluorescent AgNC. We overcame this limitation and created an AgNC-MB that functions for arbitrary target sequences by redesigning the AgNC-MB to make AgNC-stabilization independent of the bases contained in the binding domain.…”
Section: Resultssupporting
confidence: 57%
“…If bases contained within the 5′-end of the target binding domain participate in cluster formation, this insertion would destabilize the conformation of the bases and inhibit or alter cluster formation. 30 Doing so completely inhibited AgNC formation in the presence of target for all six target sequences tested (see ESI †), further supporting the notion that the 12-base AgNCstabilizing sequence requires additional bases to stabilize a fluorescent AgNC. We overcame this limitation and created an AgNC-MB that functions for arbitrary target sequences by redesigning the AgNC-MB to make AgNC-stabilization independent of the bases contained in the binding domain.…”
Section: Resultssupporting
confidence: 57%
“…For the miRNA detection assay, we mixed a fixed amount of total RNAs (5 mg) from cop1-6, hyl1-2 and wild type with the probes at the given concentrations of Tris-acetate buffer and incubated for 15 min at 25°C. Then, AgNO 3 (250 mM) and NaBH 4 (250 mM) were added to the RNA/DNA mixtures to a final volume (50 ml) (14)(15)(16)(17). All the DNA/AgNCs reactions were incubated for 1 h at 25°C and diluted with 450 ml of distilled water before measurement on a fluorimeter (Horiba Jobin Yvon, Fluoromax-4) in a 10 mm disposable cuvette.…”
Section: Methodsmentioning
confidence: 99%
“…In addition to the core processing proteins, at least 10 components have been reported that play direct or indirect roles in the intricate regulation of miRNA biogenesis [7][8][9][10][11][12][13] . To further isolate hidden components in miRNA biogenesis, we have developed a rapid and simple miRNA detection method using DNAtemplated silver nanoclusters (DNA/AgNCs) probes [14][15][16][17] . By applying this method, we isolated COP1 E3 ubiquitin ligase that negatively regulates photomorphogenesis triggered by far-red and visible light.…”
mentioning
confidence: 99%
“…Highly fluorescent AgNCs were produced with this DNA. The authors suggested that mismatched self-dimer formation might be a reason for its strong fluorescence [109]. When hybridized with a complementary microRNA sequence, significant fluorescence quenching was observed, allowing detection of such nucleic acid targets.…”
Section: Hybridization Activated Fluorescence Our Understanding On Tmentioning
confidence: 99%